1971
DOI: 10.1159/000175321
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Various Fat Supplements on the Nutritional and Pathogenic Characteristics of Diets Containing Erucic acid in Ducklings

Abstract: Diets containing rapeseed oil (RSO), or RSO supplemented with olive oil (OLO, rich in oleic acid), safflower oil (SAF, rich in linoleic acid) or tallow (TAL, comparatively rich in palmitic acid) were compared for their nutritional and pathogenic characteristics in ducklings. Unsupplemented RSO and the mixtures RSO-OLO and RSO-SAF caused growth retardation, mortality, lipidosis of the spleen cirrhotic changes of the liver and vacuolar changes of the heart and the skeletal muscles. The mixture RSO-TAL caused no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 5 publications
3
10
0
Order By: Relevance
“…That this is not the manifestation of a high fat intake per se was shown by the absence of such changes in the hearts of animals consuming similar amounts of either peanut oil or hydrogenated peanut fat. These changes are similar in some respects to the changes already reported in the hearts of different species of laboratory animals maintained on diets containing rapeseed oil [1][2][3]26]. The harmful effects were attributed to the high amounts of erucic acid found in dietary rapeseed oil.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…That this is not the manifestation of a high fat intake per se was shown by the absence of such changes in the hearts of animals consuming similar amounts of either peanut oil or hydrogenated peanut fat. These changes are similar in some respects to the changes already reported in the hearts of different species of laboratory animals maintained on diets containing rapeseed oil [1][2][3]26]. The harmful effects were attributed to the high amounts of erucic acid found in dietary rapeseed oil.…”
Section: Discussionsupporting
confidence: 86%
“…Young rats fed rapeseed oil were observed to have smaller testes and to exhibit degeneration of seminiferous tubules in males and resorption of fetuses and sterility in females [17]. Recent studies with rapeseed oil have demonstrated histopathological changes in the hearts and skeletal muscles of rats [1], ducklings [2,3], guinea pigs [30] and pigs [26]. Rapeseed oil contains high amounts of erucic acid.…”
Section: Introductionmentioning
confidence: 99%
“…All other cultivars had a high level of erucic acid, which is in partial agreement with published results. 9 It was also reported previously that Tori-7, Safal, Agrani and Rai-5 contain 46.70-51.90% erucic acid, whereas Barisarisha-8 contained the lowest amount of erucic acid (36.4%). 15,16 The stearic acid (18:0), vaccenic acid (18:1 n-7), arachidic acid (20:0), behenic acid (22:0), lignoceric acid (24:0), and nervonic acid (24:1 n-9) contents were very low without showing major variation among the genotypes.…”
Section: Resultssupporting
confidence: 55%
“…8 It has been shown in experimental animals that high intake of this type of oil may increase the content of adrenal cholesterol, may interfere with reproduction, cause fibrotic changes in myocardium and increase liver weight and liver cholesterol. 9,10 Metabolic studies have been conducted on Indian subjects to investigate the effects of using fish oils and linolenic acid (18:3 n-3) rich oils (canola oil and high erucic mustard oil) in comparison with oils those contain negligible amounts of linolenic acid (18:3) (groundnut oil and palmolein), on plasma lipids, essential fatty acid status and platelet aggregation. The results showed that at a level of 6-7 energy % linoleic (18:2 n-6), about 0.20-0.50 energy % fish oils or 1.40 energy % linolenic acid produced antiatherogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…A deficiency of palmitic acid and an excess of erucic acid were considered to be responsible for the lower nutritional value of RSO. Supplements with palm oil have also been shown to produce favourable effects on the growth and pathological responses of ducklings [16] and guinea pigs [17] fed RSO. However, it should be stressed that, in these studies, any favourable effect of palmitic acid did not exceed that of ameliorating detrimental effects primarily produced by erucic acid.…”
Section: Discussionmentioning
confidence: 99%